2006
DOI: 10.1038/nmat1635
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale avalanche photodiodes for highly sensitive and spatially resolved photon detection

Abstract: Integrating nanophotonics with electronics could enhance and/or enable opportunities in areas ranging from communications and computing to novel diagnostics. Light sources and detectors are important elements for integration, and key progress has been made using semiconducting nanowires and carbon nanotubes to yield electrically driven sources and photoconductor detectors. Detection with photoconductors has relatively poor sensitivity at the nanometre scale, and thus large amplification is required to detect l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
356
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(363 citation statements)
references
References 26 publications
7
356
0
Order By: Relevance
“…Meanwhile, PIC applications will likely necessitate electrically controllable optoelectronic devices. A few demonstrations of nanowire optoelectronics exist, but either single nanowires were removed from their native substrates [18][19][20] or nanowire ensembles were used 21,22 . Both scenarios make mass device integration extremely demanding.…”
mentioning
confidence: 99%
“…Meanwhile, PIC applications will likely necessitate electrically controllable optoelectronic devices. A few demonstrations of nanowire optoelectronics exist, but either single nanowires were removed from their native substrates [18][19][20] or nanowire ensembles were used 21,22 . Both scenarios make mass device integration extremely demanding.…”
mentioning
confidence: 99%
“…In conjunction with an electrically driven plasmon source 23 , a near-field SP detector could be integrated into a "dark" optoelectronic-plasmonic nanocircuit in which all coupling is in the near field. Moreover, the plasmon detection sensitivity could be improved by using a nanoscale avalanche photodiode 24 Approximately 30% of the SP energy is reflected, 3% scatters to the far field, 20% is absorbed by the Ge NW, and the rest is transmitted.…”
mentioning
confidence: 99%
“…Light source was assumed to have 0.6 mm in wavelength and 1 lux is 1.464 mW=m 2 . When compared to avalanche photodiode (4 pW minimum detectable power) (Hayden et al 2006), HNB photodetector showed the step of light intensity change with 11.5 pW and similar dynamic range from pW to nW with less noise. We further evaluated the performance of HNB photodetectors including responsiveness (R d ðA=W Þ ¼ dI=P in ), which is the photocurrent per unit power intensity, and EQE (%) described in Eq.…”
Section: In-plane Sensor Measurementsmentioning
confidence: 94%
“…Nanoscale photodetectors have been previously demonstrated using 1-D nanostructures such as a single as-synthesized silicon nanowire (NW) (O'brien et al 2006;Gu et al 2005) or nanotube (NT) (Wei et al 2006) though reduced surface area can negatively affect the signal-to-noise ratio. A nanoscale avalanche photodiode was developed to amplify the single photon detection efficiency Hayden et al 2006). In order to maintain the signal quality, it is advantageous to maintain the surface area exposed to light.…”
Section: Introductionmentioning
confidence: 99%